Unleashing the power of PR : - Weiner, Mark (Jossey-Bass, 2006)
Using dozens of case studies from well-known companies such as General Electric, FedEx, Procter & Gamble, Merck, Boeing, and Intel, Delahaye president and public relations scientist Mark Weiner offers a research-based model for creating and implementing public relations programs that will generate desired results and improve an organization’s ROI. Written as a highly accessible hands-on guide, Unleashing the Power of PR explains how to use market research methods to plan and evaluate public relations programs scientifically. The author explores the benefit of learning to speak to senior executives in a way that will improve communications and ultimately help strengthen PR performance and results. In addition, the book debunks common myths—such as “PR is impossible to measure!”—that undercut the effectiveness of PR and obscure its real value.